Food emulsions - McClements, David Julian (CRC Press LLC, 2011)
Food Emulsions: Principles, Practice, and Techniques, Second Edition introduces the fundamentals of emulsion science and demonstrates how this knowledge can be applied to better understand and control the appearance, stability, and texture of many common and important emulsion-based foods.